2021
DOI: 10.1039/d0ra10770k
|View full text |Cite
|
Sign up to set email alerts
|

The microstructures and mechanical properties of nanocrystalline Li2SiO3: molecular dynamics simulations

Abstract: The microstructures and mechanical properties of nanocrystalline Li2SiO3 have been investigated via molecular dynamics calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The continuous evolution of the Young's modulus indicates that the bonding between grains becomes weaker as D s decreases, which has been widely observed in several systems. 4,7,8 The anomalous mechanical softening phenomenon in bulk nanocrystalline InAs is basically consistent with the inverse Hall-Petch relation, and the corresponding D cri is 35.93 nm in the experimental scope. We further verify this finding using molecular dynamics calculations performed in LAMMPS.…”
Section: Nanoindentation and Molecular Dynamics Simulationsupporting
confidence: 76%
See 1 more Smart Citation
“…The continuous evolution of the Young's modulus indicates that the bonding between grains becomes weaker as D s decreases, which has been widely observed in several systems. 4,7,8 The anomalous mechanical softening phenomenon in bulk nanocrystalline InAs is basically consistent with the inverse Hall-Petch relation, and the corresponding D cri is 35.93 nm in the experimental scope. We further verify this finding using molecular dynamics calculations performed in LAMMPS.…”
Section: Nanoindentation and Molecular Dynamics Simulationsupporting
confidence: 76%
“…[4][5][6] With the advent of a range of non-or advanced-powder pressing techniques, the inverse Hall-Petch relation is still being widely discovered experimentally, and also theoretically using rapidly evolving computing technology. [7][8][9] At present, typical techniques that can produce dense nonstructural bulk materials with the inverse Hall-Petch relation include crystallization from amorphous solids 10,11 (CFAS; e.g. NiP and FeSiB soft magnetic composites), high-pressure torsion 12 (HPT; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Shen et al. [ 84 ] conducted a study on the mechanical properties of nano‐crystalline Li 2 SiO 3 based on variations in grain size, employing molecular dynamic calculations. Their findings indicated that when the average grain size of Li 2 SiO 3 is ≈5.12 nm, fractures initiate in a very brief time span upon the occurrence of a strain ranging from 0.39 to 0.41.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely accepted that mechanical strength of the nanocrystalline metals and ceramics less than a few tens of nanometer follows the inverse Hall–Petch relationship. [ 69–72 ] Recently, Shen et al. predicted that Young's modulus and yield strength of nanocrystalline Li 2 SiO 3 woul follow the inverse Hall‐Petch relation with a mean grain size below 7.38 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely accepted that mechanical strength of the nanocrystalline metals and ceramics less than a few tens of nanometer follows the inverse Hall-Petch relationship. [69][70][71][72] Recently, Shen et al predicted that Young's modulus and yield strength of nanocrystalline Li 2 SiO 3 woul follow the inverse Hall-Petch relation with a mean grain size below 7.38 nm. [72] This theoretical calculation suggested that Li 2 SiO 3 as an inactive buffer matrix in the L67_550 did not effectively accommodate the volume expansion of the Si phase during cycling because the grain size of Li 2 SiO 3 in L67_550 was too fine, as found in Figure 1b, to sustain the mechanical integrity of the L67_550 material.…”
Section: Figure 5amentioning
confidence: 99%